Treacle Sticks the Nucleolar Responses to DNA Damage Together - Gál, Zita; Nieto, Blanca; Boukoura, Stavroula; Rasmussen, Anna Vestergaard; Larsen, Dorthe Helena (Frontiers in Cell and Developmental Biology, 2022)
The importance of chromatin environment for DNA repair has gained increasing recognition in recent years. The nucleolus is the largest sub-compartment within the nucleus: it has distinct biophysical properties, selective protein retention, and houses the specialized ribosomal RNA genes (collectively referred to as rDNA) with a unique chromatin composition. These genes have high transcriptional activity and a repetitive nature making them susceptible to DNA damage and resulting in the highest frequency of rearrangements across the genome. A distinct DNA damage response (DDR) secures the fidelity of this genomic region, the so-called nucleolar DDR (n-DDR). The composition of the n-DDR reflects the characteristics of nucleolar chromatin with the nucleolar protein Treacle (also referred to as TCOF1) as a central coordinator recruiting several well-characterized DDR proteins in the nucleolus. In this review, we bring together data on the structure of Treacle, its known functions in ribosome biogenesis, and its involvement in multiple branches of the n-DDR to discuss their interconnection. Furthermore, we discuss how the functions of Treacle in ribosome biogenesis and in the n-DDR may contribute to Treacher Collins Syndrome, a disease caused by mutations in Treacle. Finally, we outline outstanding questions that need to be addressed for a more comprehensive understanding of Treacle, the n-DDR, and the coordination of ribosome biogenesis and DNA repair.